INVESTIGATING BRAND SWITCHING ON LOCAL COSMETICS PRODUCT (A CASE STUDY OF SOMETHINC IN MANADO) - Vinny Gloria Rooroh; Frederik G. Worang; Shinta J. C. Wangke (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
This study is to know the influence of social media marketing (X1), electronic word of mouth (X2) and price (X3) on brand switching (Y) of Somethine local cosmetics in Manado. The type of this research is quantitative research method by distributing questionnaires through 100 respendents with purposive sampling method who was the domicilie in Manado and using Somethine product for 3 months and processed the data through multiple linear regression analysis. Based on data results concluded that: social media marketing has significant influence on brand switching of somethinc local cosmethics in Manado, electronic word of mouth has significant influence on brand switching of Somethinc local cosmethics in Manado, price has significant influence on brand switching of Somethinc local cosmethics in Manado and social media marketing, electronic word of mouth and price has significant influence on brand switching of Somethinc local cosmethics in Manado. The company should be considering an affordable price for each new product that will be release with a nice, proper, and fresh advertisement, that not only shows how great the product is, but focusing on how it can affect and fulfill the customer needs.   Keyword: Social Media Marketing, Electronic Word Of Mouth, Price, Brand Switching